The go-giver leader : a little story about what matters most in business - Burg, Bob; Mann, John David (Portfolio, 2016)
"PLEASE NOTE: This book was previously published under the title It's Not About You. From the acclaimed, bestselling authors of The Go-Giver, a new parable about the power of giving leadership. The family-owned business of Allen & Augustine has manufactured high-quality chairs for decades. Its people take pride in their work and feel loyal to their owners and management team. But this long-revered company is now at a crossroads, hurt by a tough economy, foreign competition, and a cash crunch. The air is filled with the scent of uncertainty, anxiety, perhaps even panic. Enter Ben, the ambitious young executive assigned by his firm to promote a merger that will rescue Allen & Augustine. Ben's facts are undeniable: the chairmaker can either merge and modernize, or go bankrupt and vanish. So why can't he convince anyone to buy in, from the CEO on down? During his week at the company, as Ben gets to know its people and meets with its top executives, he begins to realize that his aggressive style is actually making it harder to reach his goals. As one character puts it, "How far can you push a rope?" Will Ben find a way to sway the employee shareholders before the climactic vote? And can Allen & Augustine survive without losing its soul? The answers may surprise you, as you follow Ben on his journey to understanding that the path to genuine influence lies less in taking leadership than in giving it"--